Pendampingan Belajar Kosakata Bahasa Inggris di Panti Asuhan Pondok Kasih: Pengembangan Media Pembelajaran - Ervin Suryaningsih; Esriaty Sega Kendenan; Wahyu Seno Aji (Universitas Pahlawan Tuanku Tambusai, 2023)
This article discusses English vocabulary learning medium for young learners through songs and stories inspired by the implementation of a community service program at the Pondok Kasih Orphanage, Salatiga. It aims to attract interest and motivate children to learn English. Research and Development method is used for the development of 4D (Define, Design, Develop, and Dissemination) by observation and documentation as the data collection techniques. The existing data are analyzed descriptive qualitatively. English Vocabulary media developed in this program is in the form of an audiobook which contains Indonesian children's songs that are translated into English and created in the form of stories. This medium is needed to attract and motivate children in learning English vocabulary in orphanages and young children learning communities.